AI & HR Integration in Industry 4.0: A Multidisciplinary Literature Review - Abd. Rasyid Syamsuri; Rifki Arohman; Adila Fitrisari; Rofi Gemaladi Hibatullah (Penerbit Merdeka Kreasi, 2025)
This study investigates the integration of artificial intelligence into human resource management within the context of Industry 4.0, focusing on its transformative role, challenges, and strategic implications. The primary objective is to explore how AI technologies influence recruitment, employee development, performance management, and organizational sustainability while addressing ethical and operational concerns. Using a literature review method, the research synthesizes insights from peer-reviewed journals, academic books, and reports published within the last five years, selected based on relevance, methodological rigor, and contribution to the discourse on AI-driven HRM. The findings reveal that AI enhances predictive capabilities in talent retention, enables personalized training pathways, and improves decision-making accuracy, yet it also introduces risks related to algorithmic bias, transparency, and employee resistance. The analysis emphasizes that successful AI adoption requires a hybrid approach that combines technological precision with human judgment, supported by robust governance frameworks and alignment with organizational culture. These results underscore the importance of adopting a multidisciplinary perspective to guide future research and practice, ensuring that AI integration in HRM contributes to sustainable, ethical, and human-centered organizational transformation in the era of Industry 4.0.